SOSIALISASI DAN PELATIHAN STANDARISASI KEBERSIHAN PUBLIC AREA DI LINGKUNGAN VITKA HOLDING - Supardi; Rais, Syafruddin; Lubis, Arina Luthfini; Fatimah, Zahara (PUSLITABMAS-Politeknik Pariwisata Batamc, 2024)
The community service team carries out outreach and training activities because it is beneficial for Vitka Holding employees and re-sharpens their abilities, especially in maintaining cleanliness and sanitation. This activity was carried out in collaboration with lecturers and leaders of Vitka Holding to ensure the event remained strong and on target. This service is provided by conducting socialization and training in the Batam Tourism Polytechnic's Natuna room on Friday, November 3 2023. It is hoped that by participating in this activity, employees can better understand the importance of cleanliness and proper equipment for every incident they face, and then apply this knowledge. in everyday life. Increasing cleanliness around Vitka Holding will certainly be beneficial for the foundation. This socialization and training action is a form of love carried out to improve the competence of others. This outreach and training can help staff gain an understanding of appropriate cleaning supplies and equipment for the public areas where they work. This practice is also in line with the objectives of PkM which aims to provide reciprocity to the community. This training was carried out in collaboration with the teaching team and leaders of Vitka Holding. This is intended so that project participants, in particular, gain good principles and learning through this exercise.